The Effect of Workload and Work Discipline On Organizational Commitment With Job Satisfaction As A Mediating Variable - Denis Eka Isrofah; Mei Retno Adiwaty; Ayundha Evanthi (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Organizational commitment is a key factor influencing a company's effectiveness and sustainability. PT PLN Nusantara Power UP Pacitan is a company engaged in power generation, transmission, and distribution. This study aims to explore the effect of workload and work discipline on organizational commitment, with job satisfaction as a mediating variable among employees of PT PLN Nusantara Power UP Pacitan. This research employs a quantitative method using a questionnaire for data collection. The study population consists of 247 employees, with a sample of 90 respondents selected through purposive sampling. Data analysis is conducted using the Partial Least Squares (PLS) method. The results indicate that workload has a positive but insignificant effect on organizational commitment, while work discipline has a significant positive effect on organizational commitment. Furthermore, workload significantly influences organizational commitment through job satisfaction, and work discipline also significantly affects organizational commitment through job satisfaction.